PENDAMPINGAN MASYARAKAT DALAM MEMBANGUN CITRA POSITIF DESTINASI WISATA MELALUI STORYTELLING LOKAL - Telaumbanu, Tatema; Harefa, Darmawan (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
The community service program in Hilisimaetano Tourism Village, entitled “Community Assistance in Building a Positive Destination Image through Local Storytelling”, was carried out with the aim of enhancing the community’s capacity to create a positive destination image by utilizing local narratives. This program emphasizes the empowerment of residents as the main actors in tourism promotion while simultaneously preserving cultural and environmental sustainability. The program’s methods included socialization on the importance of storytelling in destination branding, training in the creation of digital content based on local stories, on-site mentoring in delivering narratives to tourists, and evaluating the effectiveness of promotion through observation and social media analysis. The results indicate a significant increase in community understanding of storytelling as a tool for destination branding, as well as improved ability to produce authentic and engaging content. Additionally, tourists’ positive perceptions of the destination increased, reflected in higher engagement in tourism activities and greater appreciation of the unique local culture. This program not only strengthens the destination’s image but also opens new economic opportunities through creative entrepreneurship based on culture and local narratives. Overall, local storytelling guidance has proven to be an effective strategy for building the identity and positive image of Hilisimaetano Tourism Village, supporting sustainable tourism, and reinforcing the role of the local community as key actors in destination development.